Penggunaan Cytrus Orange sebagai Alternatif Menurunkan Kecemasan Pasien Hemodialisis - Yeni Kartika Sari; Okky Cintya Permata Dewi; Wahyu Wibisono; Ning Arti Wulandari (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the effect of giving citrus aromatherapy (orange) on anxiety in hemodialysis patients. This research design is pre-experimental with one group pre-post test design. The results of the study using the paired t-test obtained a p-value of 0.000. Before administering citrus aromatherapy (orange), the average anxiety score was 51.20 and after administration of citrus aromatherapy (orange) was 34.45. In conclusion, giving citrus aromatherapy (orange) affects anxiety in hemodialysis patients. Keywords: Citrus Orange, Hemodialysis, Anxiety